Mitochondrial Protein Translation: Emerging Roles and Clinical Significance in Disease - Wang, Fei; Zhang, Deyu; Zhang, Dejiu; Li, Peifeng; Gao, Yanyan (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are one of the most important organelles in cells. Mitochondria are semi-autonomous organelles with their own genetic system, and can independently replicate, transcribe, and translate mitochondrial DNA. Translation initiation, elongation, termination, and recycling of the ribosome are four stages in the process of mitochondrial protein translation. In this process, mitochondrial protein translation factors and translation activators, mitochondrial RNA, and other regulatory factors regulate mitochondrial protein translation. Mitochondrial protein translation abnormalities are associated with a variety of diseases, including cancer, cardiovascular diseases, and nervous system diseases. Mutation or deletion of various mitochondrial protein translation factors and translation activators leads to abnormal mitochondrial protein translation. Mitochondrial tRNAs and mitochondrial ribosomal proteins are essential players during translation and mutations in genes encoding them represent a large fraction of mitochondrial diseases. Moreover, there is crosstalk between mitochondrial protein translation and cytoplasmic translation, and the imbalance between mitochondrial protein translation and cytoplasmic translation can affect some physiological and pathological processes. This review summarizes the regulation of mitochondrial protein translation factors, mitochondrial ribosomal proteins, mitochondrial tRNAs, and mitochondrial aminoacyl-tRNA synthetases in the mitochondrial protein translation process and its relationship with diseases. The regulation of mitochondrial protein translation and cytoplasmic translation in multiple diseases is also summarized.